Omar Nelson Bradley papers - Bradley, Omar Nelson, 1893-1981.
Addresses, statements, and articles written by Bradley while he served as chief of staff of the U.S. Army (1948-1949) and chairman of the joint chiefs of staff (1949-1953). Subjects include the U.S. Army budget, Career Compensation Act of 1949, continuation of the Selective Service Act of 1948 and universal military training, and unification of the armed services. Other subjects include the Korean War, Military Assistance Program, Mutual Security Program (1951), North Atlantic Treaty (1949), and admission of Greece and Turkey to the North Atlantic Treaty Organization.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States; United States; United States. -- Army -- Finance; United States. -- Air Force -- Pay, allowances, etc; United States. -- Army -- Pay, allowances, etc; United States. -- Army -- Pay, allowances, etc; United States. -- Air Force -- Recruiting, enlistment, etc; United States. -- Army -- Recruiting, enlistment, etc; United States. -- Navy -- Recruiting, enlistment, etc; United States. -- Department of the Army. -- Office of the Chief of Staff; United States. -- Joint Chiefs of Staff; United States. -- National Security Training Commission; North Atlantic Treaty Organization; North Atlantic Treaty -- (1949); Draft; Korean War, 1950-1953.; Economic assistance, American; International cooperation; Military assistance, American; Military pensions -- United States; Mutual security program, 1951.; Technical assistance, American; Greece -- Foreign relations -- 1935-1967.; Turkey -- Foreign relations -- 1918-1960.; United States -- Armed Forces; United States -- Armed Forces -- Pay, allowances, etc; United States -- Armed Forces -- Recruiting, enlistment, etc; United States -- Foreign relations -- 1945-1953.; Army officers